Identification of vortex structures in a cohort of 204 intracranial aneurysms. Issue 130 (31st May 2017) - Varble, Nicole; Trylesinski, Gabriel; Xiang, Jianping; Snyder, Kenneth; Meng, Hui
Abstract : An intracranial aneurysm (IA) is a cerebrovascular pathology that can lead to death or disability if ruptured. Abnormal wall shear stress (WSS) has been associated with IA growth and rupture, but little is known about the underlying flow physics related to rupture-prone IAs. Previous studies, based on analysis of a few aneurysms or partial views of three-dimensional vortex structures, suggest that rupture is associated with complex vortical flow inside IAs. To further elucidate the relevance of vortical flow in aneurysm pathophysiology, we studied 204 patient IAs (56 ruptured and 148 unruptured). Using objective quantities to identify three-dimensional vortex structures, we investigated the characteristics associated with aneurysm rupture and if these features correlate with previously proposed WSS and morphological characteristics indicative of IA rupture. Based on the Q -criterion definition of a vortex, we quantified the degree of the aneurysmal region occupied by vortex structures using the volume vortex fraction ( vVF ) and the surface vortex fraction ( sVF ). Computational fluid dynamics simulations showed that the sVF, but not the vVF, discriminated ruptured from unruptured aneurysms. Furthermore, we found that the near-wall vortex structures co-localized with regions of inflow jet breakdown, and significantly correlated to previously proposed haemodynamic and morphologic characteristics of ruptured IAs.